“Better Late Than Never”—Late‐Onset Genotype‐Negative Congenital Long QT Syndrome: Case Report and Review - Clement Tan; Vaikunthan Thanabalasingam; Chaminda Sella Kapu; Zhihua Zhang (Clinical Case Reports, 2025)
ABSTRACT Congenital long QT syndrome (LQTS) is a genetic disorder causing prolonged QT intervals and an increased risk of arrhythmias and sudden cardiac death. With 25% of cases lacking known genetic mutations, diagnosis and treatment can be challenging. We present a successfully managed case of late‐onset genotype‐negative phenotype‐positive LQTS presenting as palpitations, complicated by a single event of polymorphic ventricular tachycardia, followed by a review of the literature. This case underscores the gaps in understanding congenital long QT syndrome, especially in genotype‐negative cases, and highlights the need for ongoing research for risk assessment and effective management to prevent fatal cardiac events.